Anti-cancer activities of pH- or heat-modified pectin - Leclere, Lionel; Van Cutsem, Pierre; Michiels, Carine (Frontiers in Pharmacology, 2013)
Despite enormous efforts that have been made in the search for novel drugs and treatments, cancer continues to be a major public health problem. Moreover, the emergence of resistance to cancer chemotherapy often prevents complete remission. Researchers have thus turned to natural products mainly from plant origin to circumvent resistance. Pectin and pH- or heat-modified pectin have demonstrated chemopreventive and antitumoral activities against some aggressive and recurrent cancers. The focus of this review is to describe how pectin and modified pectin display these activities and what are the possible underlying mechanisms. The failure of conventional chemotherapy to reduce mortality as well as serious side effects makes natural products, such as pectin-derived products, ideal candidates for exerting synergism in combination with conventional anticancer drugs.